Konsep dan Implementasi Ekoteologi dalam Kurikulum Pendidikan Agama Islam - Syukron Jamal (Yayasan Al-Afif, 2025)
Climate change, increasing pollution, scarcity of water resources, pest and disease outbreaks as a result of the global environmental crisis have become a real threat to human life, including in Indonesia. Extra and systematic efforts are needed to prevent these problems, one of which is through the instillation of environmental conservation ideology (ecoteology) through an integrated education system in the learning curriculum from elementary, secondary to higher education. This study attempts to describe and analyze the concept of ecotheology from an Islamic perspective and how its implementation is practical and integrated into the Islamic education curriculum in Indonesia so that it becomes a concrete effort to build awareness not only of environmental issues but also of the continuity of human civilization.